Pengaruh Audit Tenure Dan Ukuran Perusahaan Terhadap Kualitas Audit Perusahaan Sektor Consumer Non-Cyclicals - Febrianti, Mutiara; Keristin, Usnia Wati (MDP Student Conference, 2024)
This study aims to determine (1) the effect of audit tenure on audit quality, (2) the effect of company size on audit quality in noncyclical consumer sector companies listed on the Indonesia Stock Exchange in 2019-2022. The theory used in this research is Agency Theory. The approach used in this research is a quantitative approach. The population of this study is the consumer non cyclicals sector companies listed on the Indonesia Stock Exchange in 2019-2022. The sampling technique was purposive sampling technique. The sample used was 36 companies from 112 companies in the Consumer Goods Industry sector listed on the Indonesia Stock Exchange, so that the research data analyzed amounted to 144 data. The data analysis technique used is descriptive statistical analysis. Based on the results of the research, it shows that the Audit Tenure variable have no effect on Audit Quality. While, company size influences audit quality.